Five new species of the genus Mallinella Strand, 1906 (Araneae: Zodariidae) from Sri Lanka - Dayananda, Naruwan; Benjamin, Suresh P. (Zootaxa, 2025)
Five new species of the ant-eating spider genus Mallinella from the natural forests of Sri Lanka are described and illustrated: Mallinella dhanahami sp. nov. (male, female), M. milkyway sp. nov. (male, female), M. moncheri sp. nov. (male, female), M. oreo sp. nov. (male, female), and M. truffles sp. nov. (male, female). A key to all the known Mallinella species from Sri Lanka is provided, and their current distribution in Sri Lanka is mapped.